ETHNO-KNOWLEDGE AND BIOPRODUCTS MARKET IN MANAUS-AM - Costa, Reinaldo Corrêa; Nunez, Cecilia Veronica (Emirates Journal of Food and Agriculture, 2011)
This study aimed to survey the peasants or family farm production, lead to the bioproducts market (cosmetics and herbal), its market structures in Manaus (Amazonas, Brazil), and how they form connections that result in a rural-urban spatiality. In each production process stage, there appear economic agents linked by raw material which also adds value to the goods with Science and Technology and includes also ethno-knowledge. For this, fieldworks were done with interviews, analyzing this information crossing with phytochemistry, pharmacognosy, biology and economics information, to determine the bioproducts geographic space identification and their dimensions. The raw materials used in the bioproducts market of Manaus came from other places. The peasant societies use the biodiversity on a quotidian manner in their ways of life (which produces and how produces), which form knowledge, economic and cultural uses of biodiversity spaces legacy from nature and who are territorialized on it with their own landscapes and characteristics. Through this a better understanding of their way of life policy, economic and cultural tool, to conserve and protect natural systems to produce biodiversity for social diversity, including health public policies could be achieved.